2017
DOI: 10.4236/gep.2017.512003
|View full text |Cite
|
Sign up to set email alerts
|

Trend Analysis in Annual and Monthly Pan Evaporation and Pan Coefficient in the Context of Climate Change in Togo

Abstract: Trend analysis was performed for the long-term measured pan evaporation and estimated pan coefficient for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The Mann Kendall analysis is a statistical test widely used for analysing trends in climatologic (Abrha, 2015); (Djaman, Koudahe, & Ganyo, 2017); (Bhuyan, Islam, & Bhuiyan, 2018); (Tabari & Talaee, 2011) and hydrologic time-series studies (Yue & Wang, 2004); (Yue & Hashino, 2003). There are two advantages of using this test.…”
Section: Mann Kendallmentioning
confidence: 99%
“…The Mann Kendall analysis is a statistical test widely used for analysing trends in climatologic (Abrha, 2015); (Djaman, Koudahe, & Ganyo, 2017); (Bhuyan, Islam, & Bhuiyan, 2018); (Tabari & Talaee, 2011) and hydrologic time-series studies (Yue & Wang, 2004); (Yue & Hashino, 2003). There are two advantages of using this test.…”
Section: Mann Kendallmentioning
confidence: 99%
“…Evapotranspiration (ET), the process of water release to the atmosphere, plays a crucial role in irrigation management [1], water balance estimation [2], surface runoff estimation [3], groundwater level prediction [4], water stress assessment [5], reservoir management [6], daily flux modelling [7], and climate change impact assessment [8]. It determines the crop irrigation requirement and thus, irrigation management, the introduction of new crop, or crop scheduling to adapt to climate change [9][10][11]. It is a major component that defines surface runoff and therefore, important for designing drainage and hydraulic structure [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Most recent studies have revealed increasing, decreasing or no trend in rainfall amounts indicating the influence of climate change over rainfall (in the case of regions showing increasing or decreasing trends) or no influence (regions showing no trends). A few studies have also reported statistical trends in rainy days, evaporation rates, air temperature and extreme rainfall events correlated with climate change scenarios (Xu et al, 2006;Burn & Hesch, 2007;Bandyopadhya et al, 2009;Fu et al, 2009;Kumar & Jain, 2010, 2011Abtew et al, 2011;Jhajharia et al, 2012;Soltani et al, 2012;Kumar et al, 2012;Madhu et al, 2015;Soro et al, 2016;Djaman et al, 2017;Oliveira et al, 2017;Toride et al, 2018;Yang et al, 2019;Behzadi et al, 2020). The statistical trend results provide evidence for climate change effects on parameters analyzed and its contribution to regional climatic changes.…”
Section: Introductionmentioning
confidence: 78%